Challenges and Constraints in Irrigation Practices in Mahabubnagar District: Analyzing Socioeconomic, Environmental, and Technical Factors (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the challenges and constraints in irrigation practices within the Mahabubnagar district, with a focus on socioeconomic, environmental, and technical factors. The district, characterized by semi-arid conditions, relies heavily on agriculture, making efficient irrigation critical for its socioeconomic development. The research employs a mixed-methods approach, combining quantitative surveys with qualitative interviews, to comprehensively assess the multifaceted challenges faced by local farmers. Data was collected from a representative sample of 200 households across different villages, capturing diverse perspectives on irrigation practices. The findings reveal significant socioeconomic challenges, including limited access to financial resources, inadequate infrastructure, and fragmented land holdings, which hinder the adoption of modern irrigation technologies. Environmental factors, such as erratic rainfall, groundwater depletion, and soil degradation, exacerbate these issues, leading to inefficient water use and reduced agricultural productivity. Additionally, technical constraints, including the lack of access to advanced irrigation equipment and insufficient technical knowledge among farmers, further contribute to suboptimal irrigation practices. The study concludes with recommendations for policymakers to address these challenges through targeted interventions, including improving access to credit, enhancing infrastructure, promoting sustainable water management practices, and providing technical training to farmers. The implications of these findings extend beyond Mahabubnagar, offering valuable insights for other semi-arid regions facing similar irrigation challenges.